Chemotaxis of 3T3 and SV3T3 cells to fibronectin is mediated through the cell-attachment site in fibronectin and a fibronectin cell surface receptor (The Rockefeller University Press, 1987)
Fibronectin (FN) is a multidomain extracellular matrix protein that induces attachment and chemotactic migration of fibroblastic cells. In this study we analyzed the molecular determinants involved in the FN- induced chemotactic migration of normal and SV40-transformed 3T3 cells. Two different monoclonal antibodies to the cell-binding site of FN blocked chemotaxis to a 140-kD FN fragment (Ca 140) containing the cell- binding domain. A monoclonal antibody to a determinant distant from the cell-binding site did not affect chemotaxis. A synthetic tetrapeptide, RGDS, which represents the major cell-attachment sequence, was able to compete with FN and the Ca 140 fragment in chemotaxis assays, but this peptide itself had no significant chemotactic activity. A larger peptide encompassing this sequence, GRGDSP, was chemotactic, while the peptide GRGESP, where a glutamic acid residue was substituted for aspartic acid, was inactive. Chemotactic migration could be prevented in a dose-dependent manner by a rabbit polyclonal antiserum to a 140-kD cell surface FN receptor. This antibody was more effective on normal than on transformed 3T3 cells. Neither the anti-FN receptor antiserum nor a monoclonal antibody to the cell-binding site of FN blocked migration induced by another potent chemoattractant, platelet-derived growth factor. These data indicate that FN-induced chemotaxis of 3T3 and SV3T3 cells is mediated via the RGDS cell-attachment site of FN and the 140-kD cell surface FN receptor. The interaction is specific and can be altered by transformation.